1975
DOI: 10.1073/pnas.72.4.1622
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic effector cells specific for B Cell lines transformed by Epstein-Barr virus are present in patients with infectious mononucleosis.

Abstract: Peripheral lymphoid cells, from 12 cases of acute infectious mononucleosis (IM), were tested in a micro chromium-51 release assay for cytotoxic activity against a variety of cell lines that did or did not carry the Epstein-Barr virus (EBV) genome. Unfractionated lymphocytes from these patients were cytotoxic to both types of cell lines, as were lymphocytes from healthy individuals. If, however, lymphocytes bearing complement receptors were removed, the residual IM lymphocyte fraction was specifically cytotoxic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
95
4

Year Published

1977
1977
1996
1996

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 321 publications
(103 citation statements)
references
References 17 publications
4
95
4
Order By: Relevance
“…Interestingly, our findings contrast with those of others who, using cytotoxic T cells from patients with acute infectious mononucleosis (IM), found no HLA-associated killing-of EBV-infected target cells (14,15) or HLA-associated killing but no allogeneic restriction (16). It should be emphasized, however, that although EB virus-specific memory T cells have been readily demonstrated in normal seropositive donors, they have not been detected in IM patients until at least 5-23 weeks after onset (17).…”
contrasting
confidence: 56%
“…Interestingly, our findings contrast with those of others who, using cytotoxic T cells from patients with acute infectious mononucleosis (IM), found no HLA-associated killing-of EBV-infected target cells (14,15) or HLA-associated killing but no allogeneic restriction (16). It should be emphasized, however, that although EB virus-specific memory T cells have been readily demonstrated in normal seropositive donors, they have not been detected in IM patients until at least 5-23 weeks after onset (17).…”
contrasting
confidence: 56%
“…Several reports have shown that during IM the percentage of peripheral blood CD8 + lymphocytes increases while the percentage of CD4 + lymphocytes decreases (Reinherz et al, 1980;De Waele et al, 1981). Both CD4 ÷ and CD8 + subsets are activated, as determined by the upregulation of surface CD45RO (Miyawaki et al, 1991), and EBV-specific cytotoxic T lymphocytes (CTLs) can be detected (Svedmyr & Jondal, 1975;Royston et al, 1975). IM is usually self-limiting, and the relative levels of CD4 + and CD8 + T cells return to normal during convalescence (Reinherz et al, 1980).…”
mentioning
confidence: 99%
“…Nkrumah et al (1976) reported that patients with Burkitt's lymphoma showed a positive skin reaction against a membrane extract of Raji cell, aind that the antigenic specificities of such reactivity did not appear to be directed against EBNA. Cytotoxic effector cells specific for Raji cells have also been found in the peripheral blood of patients with infectious mononucleosis during the acute phase of the disease (Svedmyr and Jondal, 1975). It seems possible from these studies and from others with animal tumour viruses (Habel, 1969) that there may exist a new class of plasmamembrane-associated EBV antigens which has not yet been defined serologically.…”
mentioning
confidence: 92%